Analisis Politik Hukum Pariwisata Indonesia dan Dampaknya terhadap Kebijakan Keimigrasian - Yasir Yasir (Syntax Corporation Indonesia, 2025)
The high The politics of tourism law in Indonesia greatly influences immigration policy. The politics of tourism law in Indonesia has resulted in a very large acceptance of the entry of foreigners. One of the functions of immigration is to facilitate community welfare development, which has given rise to demands for the Directorate General of Immigration to provide policies that support the international tourism sector. Various immigration facilitation policies such as free visas and ease of applying for visas are implemented to support increasing the country's foreign exchange in the tourism sector. Empirical Juridical Research with a legislative approach analyzed using Legal Theory in Policy Orientation produces the following conclusions: a) Indonesian tourism legal politics currently applies with two approaches, namely culture and economics, but the two are not carried out in a balanced manner so that tourism legal politics actually becomes culture as a potential or resources that can be utilized for economic benefits but are not followed by real efforts to preserve or sustain tourism, b) Indonesian tourism legal politics greatly influences the direction of immigration policy in Indonesia, this is shown by: Visa Free Visit Policy, Immigration Ease Policy for Foreign Investors and Tourists, Beware of Overtourism, and Challenges of Strengthening Supervision of Foreigners.